Analisa parameter pada pemotongan plate menggunakan CNC fiber laser cutting terhadap kekasaran permukaan - Muhammad Arief Hidayat; Akhmad Farid; Purbo Suwandono (Universitas Muhammadiyah Metro, 2021)
With the advancement of advanced equipment, Computer Numerical Control (CNC) laser cutting as a manufacturing tool in plate cutting, where industri player make to get maximum result. Laser cutting Cutting is one of the tools used by the industrial world to maximize cutting results. The purpose of this research To find out the results of the difference using the parameters of air pressure and cutting speed on a Q235B carbon steel plate with a thickness of 3 mm using CNC fiber laser cutting on the surface roughness of the material. The method used in this study is a real experimental research method and data analysis to analyze parameters on plate cutting using laser cutting on surface roughness with this number of experiments 9 and 3 replications for the research process by testing surface roughness using Surface Roughness Sj – 210 Mitutoyo. The results showed that the higher the air pressure and the lower the cutting speed, the lower the surface roughness value and vice versa. The lowest surface roughness value is at air pressure of 16 Bar with a cutting speed of 3300/min which is getting a value of 1.499 μm and the highest surface roughness value is at air pressure of 12 bar with a cutting speed of 3400 mm/min which is getting a value of 2.986 μm. dengan kecepatan pemotongan 3400 mm/min yaitu mendapatkan nilai sebesar 2,986 μm.